(Table 1) Radionuclides and ESR dating of sediment cores PS1535-10 and PS1535-8, supplementary data to: Hoffmann, Dirk; Woda, Clemens; Strobl, Christopher; Mangini, Augusto (2001): ESR-dating of the Arctic sediment core PS1535 dose-response and thermal behaviour of the CO-2-signal in foraminifera. Quaternary Science Reviews, 20(5-9), 1009-1014 - Hoffmann, Dirk; Woda, Clemens; Strobl, Christopher (PANGAEA - Data Publisher for Earth & Environmental Science, 2001)
ESR-spectra of foraminifera in arctic sediment cores display the [CO2]- -signal (g=2.0006). Research on the thermal behaviour of the [CO2]- -signal shows that both natural and artificial irradiation generates a precursor and a thermal unstable component of the [CO2]- -signal. The precursor can be transfered to the stable radical, and unstable radicals can be removed by heating. The signal-change by heating depends on the irradiation dose. Because of the varying response on thermal treatment, the dose-response curves show systematic differences depending on the applied procedure (single- or multi-aliquot method with or without heating). A model for the description of the [CO2]- -signal-change is presented. The combination of two exponential saturation functions seems to be an adequate analytical description of the dose-response curve of the [CO2]- -signal in foraminifera. Due to the limited thermal stability this signal can be used for dating foraminifera with ages up to about 190 ka.
This dataset is supplement to doi:10.1016/S0277-3791(00)00059-7
Keywords: Datensammlung